Factor mr + ns – nr – ms?

NetherCraft 0

I need some major help with this algebra question. Thanks for your time! 😀

3 Answers

  • mr + ns – nr – ms

    bring similar terms together

    mr – ms – nr + ns

    take out similar factors in each pair of terms

    m(r – s) -n (r – s)

    (m – n) (r – s)

  • mr + ns – nr – ms

    mr – nr + ns – ms rearrange

    r(m-n) + s(n-m) factor

    CHECK

    m = 5

    r = 2

    n = 6

    s = 12

    mr + ns – nr – ms

    (5)(2) + (6)(12) – (6)(2) – (5)(12)

    = 10 + 72 – 12 – 60

    = 82 – 12 = 70 – 60 = 10

    r(m – n) + s(n-m)

    2(5-6) + 12(6-5)

    = 2(-1) + 12(1)

    = -2 + 12

    = 10

  • m ( r – s ) – n ( r – s )

    ( r – s ) ( m – n )

Also Check This  Arrange these compounds from fastest sn2 reaction rate to slowest sn2 reaction rate.

Leave a Reply

Your email address will not be published. Required fields are marked *